2005
DOI: 10.1681/asn.2004121053
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic Blood Volume Monitoring in Ambulatory Hemodialysis Patients

Abstract: Complications related to inadequate volume management are common during hemodialysis. This trial tested the hypothesis that availability of an intradialytic blood volume monitoring (IBVM) device improves fluid removal, reducing morbidity. A six-center, randomized trial with 6 mo of intervention comparing IBVM using Crit-Line versus conventional clinical monitoring was conducted. The average rate of non-access-related hospitalizations was compared across treatment groups using Poisson regression. Mortality anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
169
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 22 publications
1
169
3
1
Order By: Relevance
“…Accordingly, monthly monitoring of RPV and home BP may offer an attractive way to assess the adequacy of volume control among HD patients. To note, the multicenter randomized Crit-Line Intradialytic Monitoring Benefit (CLIMB) trial 107 demonstrated that RPV-guided therapy was associated with worse outcomes, contrary to the original hypothesis. The CLIMB trial randomized 227 HD patients to RPV monitoring and 216 to conventional monitoring for 6 months to test the hypothesis that RPV-guided monitoring would result in reduced hospitalization rates.…”
Section: Dry Weight and Outcomesmentioning
confidence: 89%
“…Accordingly, monthly monitoring of RPV and home BP may offer an attractive way to assess the adequacy of volume control among HD patients. To note, the multicenter randomized Crit-Line Intradialytic Monitoring Benefit (CLIMB) trial 107 demonstrated that RPV-guided therapy was associated with worse outcomes, contrary to the original hypothesis. The CLIMB trial randomized 227 HD patients to RPV monitoring and 216 to conventional monitoring for 6 months to test the hypothesis that RPV-guided monitoring would result in reduced hospitalization rates.…”
Section: Dry Weight and Outcomesmentioning
confidence: 89%
“…26 Methods, baseline characteristics, and results of the CLIMB Study were reported previously. 26 Entry criteria included age between 18 and 85 years, ESRD duration for 2 months or longer, and treatment with in-center hemodialysis 3 times weekly.…”
Section: Patient Populationmentioning
confidence: 99%
“…The latter occurs because, as shown in figure 1, the rate of change in blood volume with extracellular fluid removal is the same above and below normal hydration. Misinterpretation of BVM traces may have contributed to the higher mortality observed in patients randomised to receive optional BVM measurements in the CLIMB study (Reddan et al, 2005). With adequate training, BVM can help in the assessment of fluid status but it is best used to identify and implement fluid removal strategies that minimise symptoms.…”
Section: Continuous Blood Volume Monitoringmentioning
confidence: 99%